x + 28 × x + 15 × x – x × 2 = 48,6 + 203,4 6,28 × x + x × 3,72 = 182,4 34,8 ÷ y = 10 25/08/2021 Bởi Eloise x + 28 × x + 15 × x – x × 2 = 48,6 + 203,4 6,28 × x + x × 3,72 = 182,4 34,8 ÷ y = 10
Đáp án+Giải thích các bước giải: $a/$ `x+28×x+15×x-x×2=48,6+203,4` `\to x×(1+28+15-2)=252` `\to x×(29+13)=252` `\to x×42=252` `\to x=252:42` `\to x=6` Vậy `x=6` $b/$ `6,28×x+x×3,72=182,4` `\to x×(6,28+3,72)=182,4` `\to x×10=182,4` `\to x=182,4:10` `\to x=18,24` Vậy `x=18,24` $c/$ `34,8:y=10` `\to y=34,8:10` `\to y=3,48` Vậy `y=3,48` Bình luận
`a ) x + 28 × x + 15 × x – x × 2 = 48,6 + 203,4` `x × 1 + 28 × x + 15 × x – x × 2 = 252` `( 1 + 28 + 15 – 2 ) × x = 252` `42 × x = 252` `x = 252 : 42` `x = 6` `b ) 6,28 × x + x × 3,72 = 182,4` `( 6,28 + 3,72 ) × x = 182,4` `10 × x = 182,4` `x = 182,4 : 10` `x = 18,24` `c ) 34,8 : y = 10` `y = 34,8 : 10` `y = 3,48` `#dtkc` Bình luận
Đáp án+Giải thích các bước giải:
$a/$
`x+28×x+15×x-x×2=48,6+203,4`
`\to x×(1+28+15-2)=252`
`\to x×(29+13)=252`
`\to x×42=252`
`\to x=252:42`
`\to x=6`
Vậy `x=6`
$b/$
`6,28×x+x×3,72=182,4`
`\to x×(6,28+3,72)=182,4`
`\to x×10=182,4`
`\to x=182,4:10`
`\to x=18,24`
Vậy `x=18,24`
$c/$
`34,8:y=10`
`\to y=34,8:10`
`\to y=3,48`
Vậy `y=3,48`
`a ) x + 28 × x + 15 × x – x × 2 = 48,6 + 203,4`
`x × 1 + 28 × x + 15 × x – x × 2 = 252`
`( 1 + 28 + 15 – 2 ) × x = 252`
`42 × x = 252`
`x = 252 : 42`
`x = 6`
`b ) 6,28 × x + x × 3,72 = 182,4`
`( 6,28 + 3,72 ) × x = 182,4`
`10 × x = 182,4`
`x = 182,4 : 10`
`x = 18,24`
`c ) 34,8 : y = 10`
`y = 34,8 : 10`
`y = 3,48`
`#dtkc`